Lighting the way or stealing the shine? An examination of the duality in star scientists' effects on firm innovative performance - Kehoe, Rebecca R.; Tzabbar, Daniel (Strategic Management Journal, 2015)
Do star employees enhance or constrain the innovative performance of an organization? Using data from 456 biotechnology firms between 1973 and 2003, we highlight the duality of the effects that stars have on firm performance. We show that while stars positively affect firms' productivity, their presence constrains the emergence of other innovative leaders in an organization. We find that firm productivity and innovative leadership among non‐stars in a firm are greatest when a star has broad expertise and collaborates frequently. We offer cross‐disciplinary insights into the role of human capital as a source of competitive advantage, suggesting that the value of human capital in a firm is contingent on the mutual dependence inherent in high‐status employees' relationships with other individuals in a firm . Copyright © 2014 John Wiley & Sons, Ltd.